Are individuals with autism spectrum disorders sensitive to traits? - Ramachandran, Rajani (2007)
This thesis examined whether individuals with Autism Spectrum Disorders are sensitive to traits. The ability of individuals with Autism Spectrum Disorders to infer traits from descriptions of behaviour was investigated by asking participants to read trait implying sentences and then to chose one of two words that best related to the sentence. In experiment 1, individuals with Autism Spectrum Disorders performed similarly to matched controls in being faster at choosing the trait in comparison to the semantic associate of one of the words in the sentence. The results from experiments 1 and 2 provided converging evidence in suggesting that inferring traits from textual descriptions of behaviour occurs with relatively little effort. The results of experiment 3 suggested that making trait inferences took priority over inferring actions or making semantic connections between words. Experiment 4 investigated whether individuals with Autism Spectrum Disorders associated the inferred trait with the person carrying out the behaviour (actor). Participants were presented with a pair of faces and sentences followed by the same pair of faces being presented with a single word. Participants had to choose which actor is best described by the word. The results provided evidence that participants with Autism Spectrum Disorders were able to associate inferred traits with the actor easily, even when the actor was represented by his face. The experiments described in this thesis provide evidence for the possibility of trait inference as relating to behaviour being a spared socio-cognitive function in autism.